PEDAGOGICAL ASPECTS OF FORMING STUDENTS ' COMPETENCE TO UNDERSTAND HISTORICAL REALITY AND EXPLAIN IT IN LOGICAL COHERENCE - Kabulov Sahab Abduqahharovich (Galaxy International Interdisciplinary Research Journal, 2023)
In this article in order to build a socially just society of pedagogical conditions of students-young people to understand the historical reality and explain it logically, to develop historical thinking, to educate them as well-rounded individuals with intellectual potential, to build a socially just society the development of growth through pedagogical and psychological means of influence is highlighted.